The digital spectator activities of Twitter users on the issue of the anti-terrorism bill in the Philippines - Shane Vallery Alipio Beduya; Diane Nicole Quebec De Leon; Jasmine Palce Quintana; Reena Anne Galang Alenzuela; Cyrra Rey-Anne Mae Megu Dela Rosa Mira; Andrea Maye Pereda Afan (Universitas Trunojoyo Madura, 2022)
Throughout history, activism has evolved with the rise of digital technologies. Individuals and groups can now conduct political activities on social media platforms. Existing studies about hashtag activism typically centered on race and gender, which are usually contextualized in the West. This study addresses the insufficient research about online activism related to policymaking in the Philippine context and focuses on online activism towards the issue of the Anti-Terrorism Bill (ATB) of 2020 that concerns potential harm to freedom of speech, expression, or of the press. This research was inspired by George and Leidner’s (2019) Hierarchy of Digital Activism, notably the Digital Spectator activism. The researchers utilized data mining approach to collect data sets scraped from Twitter. The data was acquired by using TWINT and extracting Twitter’s visible measure of interaction such as likes, retweets, and replies. These data were used to analyze Twitter users’ online activism during the heightened discussion of ATB that showed negative views of the bill using the topmost hashtag, #junkterrorbillnow and the five dominant themes: law-making process, human security, the role of social media, dialogue, and related issues. Findings also showed a link between #junkterrorbillnow and the dominant themes, and the digital spectator activities.